Causal association of epigenetic aging and COVID-19 severity and susceptibility: A bidirectional Mendelian randomization study - Xu, Wenchang; Zhang, Fengjun; Shi, Yingzhou; Chen, Yuanzhen; Shi, Bin; Yu, Gongchang (Frontiers in Medicine, 2022)
Observational data from China, the United States, France, and Italy suggest that aging is an adverse COVID-19 outcome risk factor, with older patients having a higher severity and mortality rate than younger patients. Most studies have gotten the same view. However, The role of aging in COVID-19 adverse effects is unclear. To more accurately assess the effect of age on adverse COVID-19, we conducted this bidirectional Mendelian randomization (MR) study. Epigenetic clocks and telomere length were used as biological indicators of aging. Data on epigenetic age (PhenoAge, GrimAge, Intrinsic HorvathAge, and HannumAge) were derived from an analysis of biological aging based on GWAS data. The telomere length data are derived from genome-wide association studies (GWAS) and the susceptibility and severity data are derived from the COVID-19 Host Genetics Initiative. Firstly, epigenetic age and telomere length were used as exposures, and following a screen for appropriate instrumental variables, we used random-effects inverse variance weighting (IVW) for the main analysis, and combined with other analysis methods (e.g., MR Egger, Weighted median, simple mode, Weighted mode) and multiple sensitivity analysis (heterogeneity analysis, horizontal multiplicity analysis, "leave-one-out" analysis). For reducing false-positive rates, Bonferroni corrected significance thresholds were used. A reverse Mendelian randomization analysis was subsequently performed with COVID-19 susceptibility and severity as the exposure. The results of the MR analysis showed no significant differences in susceptibility to aging and COVID-19, suggesting that age is not a risk factor for COVID-19 infection(P-values are in the range of 0.05-0.94). At the same time, we found that age was not a risk factor for increased severity of COVID-19 (P >0.05). However, severe COVID-19 can cause telomere lengths to become shorter(beta= -0.01 ; se=0.01; P=0.02779). In addition to this, severe COVID-19 infection can slow the acceleration of the epigenetic clock “GrimAge” (beta = -0.24, se = 0.07, P = 0.00122), which may be related to the closely correlation of rs35081325 and COVID-19 severity. Our study provides partial evidence for the causal effects of aging on susceptibility and severity of COVID-19.